Internalisasi Nilai Religius Islam dalam Pembelajaran Pjok: Studi Kasus Materi Kesehatan di Sekolah Dasar: Penelitian - Puji Rahayu; Sunhaji (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to analyze the concepts, strategies, and implications of the integration of Islamic religious values in Physical Education, Sports, and Health (PJOK) learning on health material at the elementary school level. This descriptive qualitative study was conducted at SD Negeri 3 Karangcengis with PJOK Teachers, PAI Teachers, and students as subjects, collecting data through triangulation methods (observation, interviews, and documentation studies) and analyzed using the Miles & Huberman interactive model. The results show that this integration focuses on the internalization of two dominant values: Thaharah (cleanliness) and Tawazun (moderation/balance), which are implemented through consistent modeling strategies and reinforcement of spiritual narratives by teachers. The key finding is a significant increase in students' discipline and personal responsibility for their health, because the intrinsic spiritual motivation that arises from the internalization of values is proven to be much more effective as a mediating factor, successfully bridging health knowledge to concrete actions (healthy living behavior) that is sustainable. Therefore, this study concludes that the integration of religious values is an effective holistic learning strategy and proposes a new theoretical modification that emphasizes the role of spiritual motivation as a key driver of healthy behavior change in elementary school-aged children, supporting the strengthening of the eight dimensions of the graduate profile.